Maximizing Performance: Work Environment, Career Development, and Motivation Dynamics: Meningkatkan Kinerja Karyawan: Dampak Lingkungan Kerja, Pengembangan Karir, dan Motivasi - Moch Alfin Basyar; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aimed to investigate the influence of work environment, career development, and motivation on employee performance. The research was conducted at a private organization, using a sample of 66 employees. Data collection involved distributing questionnaires and employing the IBM SPSS version 16 program for analysis. The findings from the F and T tests indicated that work environment, career development, and motivation had both individual and combined effects on employee performance. This study emphasizes the significance of fostering a conducive work atmosphere, facilitating career growth opportunities, and nurturing employee motivation to optimize organizational performance. The implications of these findings highlight the importance of prioritizing these factors within organizations to achieve sustained success and competitiveness in the global economy. Highlights: The study examines the impact of work environment, career development, and motivation on employee performance. The research adopts a quantitative approach, using data processing and analysis through the IBM SPSS version 16 program. The findings demonstrate that work environment, career development, and motivation have both individual and combined effects on employee performance. Keywords: employee performance, work environment, career development, motivation, quantitative research